Evaluating the critical safety factors causing accidents in high-rise building projects - Manzoor, B. (Ain Shams University, 2021)
The Malaysian construction industry plays a vital role in the economic growth of the country. However, on the other side, the annually increasing number of fatality and accidental rates on the construction sites are a serious concern, and statistics are alarming. This study has been administered with the help of questionnaire survey comprising of ten groups, including sixty-two critical safety factors. These factors were identified from the literature, and questionnaire feedback was collected from contractors, clients and consultants for this study. The outcome of this study revealed that the âfall from roofs/floor (working at height or open edges without using fall-protection systems)â is the topmost critical factor among the identified high ranked ten critical safety factors, which usually causes accidents in high-rise building projects. This study gives a clear picture of critical safety factors with practical knowledge to construction safety managers which would make the execution of building projects safer. Â© 2021 THE AUTHORS